Eskalasi Aktivitas Fisik dan Keterampilan Motorik Anak Melalui Permainan Olahraga Usia Dini - Arifah, Nurul Hikam; Harfah, Muhammad Farhan Kholidi; Wahyuningtias, Rahmaniar; Mustar, Yetty Septiani (Universitas Negeri Surabaya, 2023)
Early childhood, particularly between the ages of 0-6 years, requires special consideration in their motor development, including enrolling children in various enjoyable physical activity programs. This community service activity intends to increase children's physical and motor activity through sports games among Pelita Hati Integrated Early Childhood Post (PPT) and Bhakti Putra Kindergarten students. The method used in community service activities is lectures, discussions, workshops, and school mentoring. The implementation of these activities revealed that students were enthusiastic about participating in the entire series of activities and that teachers and parents understood the significance of physical activity programs through various sports games in enhancing children's gross motor development. Through these community services, schools and parents are aware that this activity can positively impact children's physical, motor, social, emotional, cognitive, creative, language, behavior, sensory acuity, and mental development. In addition, teachers and parents also committed to engaging in regular sports games and activities for students to enhance the children's motor development.